A critical appraisal of ibrutinib in the treatment of mantle cell lymphoma and chronic lymphocytic leukemia - Tucker DL; Rule SA (Dove Medical Press, 2015)
David L Tucker, Simon A Rule Department of Haematology, Plymouth Hospitals NHS Trust, Plymouth, UK Abstract: Although chemo-immunotherapy remains at the forefront of first-line treatment for mantle cell lymphoma (MCL) and chronic lymphocytic leukemia (CLL), small molecules, such as ibrutinib, are beginning to play a significant role, particularly in patients with multiply relapsed or chemotherapy-refractory disease and where toxicity is an overriding concern. Ibrutinib is a first-in-class, oral inhibitor of Bruton’s tyrosine kinase, which functions by irreversible inhibition of the downstream signaling pathway of the B-cell receptor, which normally promotes cell survival and proliferation. Early clinical trials have demonstrated excellent tolerability and a modest side-effect profile even in elderly and multiply pretreated patient cohorts. Although the majority of disease responses tend to be partial, efficacy data have also been encouraging with more than two-thirds of patients with CLL and MCL demonstrating a durable response, even in the high-risk disease setting. Resistance mechanisms are only partially understood and appear to be multifactorial, including the binding site mutation C481S, and escape through other common cell-signaling pathways. This article appraises the currently available data on safety and efficacy from clinical trials of ibrutinib in the management of MCL and CLL, both as a single agent and in combination with other therapies, and considers how this drug is likely to be used in future clinical practice. Keywords: ibrutinib, mantle cell lymphoma, chronic lymphocytic leukemia, Bruton’s tyrosine kinase, lymphoproliferative disorders